Growth Patterns in Seedling Roots of the Pincushion Cactus Mammillaria Reveal Trends of Intra- and Inter-Specific Variation - González-Sánchez, José de Jesús; Santiago-Sandoval, Itzel; Lara-González, José Antonio; Colchado-López, Joel; Cervantes, Cristian R.; Vélez, Patricia; Reyes-Santiago, Jerónimo; Arias, Salvador; Rosas, Ulises (Frontiers in Plant Science, 2021)
Genetic mechanisms controlling root development are well understood in plant model species, and emerging frontier research is currently dissecting how some of these mechanisms control root development in cacti. Here we show the patterns of root architecture development in a gradient of divergent lineages, from populations to species in Mammillaria. First, we show the patterns of variation in natural variants of the species Mammillaria haageana. Then we compare this variation to closely related species within the Series Supertexta in Mammillaria (diverging for the last 2.1 million years). Finally we compared these patterns of variation to what is found in a set of Mammillaria species belonging to different Series (diverging for the last 8 million years). When plants were grown in controlled environments, we found that the variation in root architecture observed at the intra-specific level, partially recapitulates the variation observed at the inter-specific level. These phenotypic outcomes at different evolutionary time-scales can be interpreted as macroevolution being the cumulative outcome of microevolutionary phenotypic divergence, such as the one observed in Mammillaria accessions and species.